EVALUATION OF BODY IMAGE IN LATINAMERICAN WOMEN LIVING IN GUIPÚZCOA. A EXPLORATORY STUDY - Rodríguez, Susana; Cruz, Soledad (Anales de Psicología / Annals of Psychology, 2006)
The aim of the present study is to know the differences in the aesthetic model and the level of body satisfaction between latinoamerican (living in Guipúzcoa) and spanish women. The sample is composed of 64 women (34 latinoamerican and 30 spanish) from 18 to 38 years old. The instruments administrated were Siluettes Test (based on the Contour Drawing Rating Scale, Thompson y Gray, 1995), a Body Satisfaction Scale (adapted from Maganto, Cruz, del Río y Roiz, 2002), the Body Shape Questionnaire (BSQ, adapted from Raich, Mora, Soler, Ávila, Clos y Zapa-ter, 1996), and a adaptation from the Body Image Ideal Questionnaire (BIIQ, Cash y Szymanski, 1995). Results show that there is not differences in the ideal siluette chosen, and that the levels of body satisfaction with the global physical aspect and with the inferior torso are higher in latino-american than in spanish women. Finally, the BMI of latinoamerican women who are satisfied is lower than the spanish women.